Properties and applications of phytepsins from thistle flowers - Vairo Cavalli, Sandra Elizabeth (2013)
Aqueous extracts of thistle flowers from the genus Cynara—Cardueae tribe Cass. (Cynareae Less.), Asteraceae Dumortier—are traditionally used in the Mediterranean region for production of artisanal cheeses. This is because of the presence of aspartic proteases (APs) with the ability to coagulate milk. Plant APs, collectively known as phytepsins (EC 3.4.23.40), are bilobed endopeptidases present in an ample variety of plant species with activity mainly at acidic pHs, and have two aspartic residues located on each side of a catalytic cleft that are responsible for catalysis. The cleavage of the scissile peptide-bond occurs primarily between residues with large hydrophobic side-chains. Even when aspartylendopeptidase activity in plants is normally present at relatively low levels overall, the flowers of several species of the Cardueae tribe possess APs with extremely high specific activities in certain tissues. For this reason, in the last two decades, APs present in thistle flowers have been the subject of intensive study. Present here is a compilation of work that summarizes the known chemical and biological properties of these proteases, as well as their biomedical and biotechnological applications.